The consequences of not using the Manchester protocol correctly in Urgent and Emergency services (Research, Society and Development, 2022)
Introduction: The Manchester Risk Classification System (MCHR) was developed in the United Kingdom by physicians and nurses with the purpose of prioritizing emergency care according to higher-risk clinical criteria in order to minimize harm to the patient's health. Objectives: To identify the main difficulties and clinical outcomes during the use of SMCR. Methodology: Integrative literature review by searching the PUBMED and SciELO databases, using the descriptors "Manchester triage" and "emergency" and their variations in English. Articles published between 2017 to 2022, which answered the research question and free full texts were included. In the end, a sample of 16 articles was obtained. Results And Discussion: Three thematic categories were listed. The first one corresponded to the clinical profile of patients screened by the RRMS, which indicated the prevalence of male patients in the white and red categories, and the most prevalent comorbidities in the red category were associated with diabetes mellitus and hypertension. Another category highlighted the main difficulties associated, which were the lack of standardization, nursing staff with no previous training, and lower performance of the triage as the patient's level of complexity increased. The last category pointed out that the RMCMS is a good predictor of mortality. CONCLUSION: There are several factors that hinder the screening process, and it is necessary that institutions promote training of healthcare professionals to improve screening standardization protocols, in order to generate a lower error rate and reduce morbidity and mortality.